Phylogenetic Tree from the BEAST analysis of Dytiscidae - Aurélie Désamoré; Benjamin Laenen; Johannes Bergsten; Kelly B. Miller (Stockholm University, 2017)
Phylogenetic Tree from the BEAST analysis of the Dytiscidae family. (http://beast.community), (Drummond AJ, Suchard MA, Xie D & Rambaut A (2012) Bayesian phylogenetics with BEAUti and the BEAST 1.7 Molecular Biology And Evolution 29: 1969-1973)
The file can be viewed as a txt or can be opened in FigTree (http://tree.bio.ed.ac.uk/software/figtree/)
Keywords: Evolutionary Biology; Evolutionary Biology; Evolutionsbiologi